Use of suction during endoscopic ultrasound-guided fine needle biopsy of solid pancreatic lesions with a Franseen-tip needle: a pilot comparative trial - Costa-Moreira, Pedro; Vilas-Boas, Filipe; Martins, Diana; Moutinho-Ribeiro, Pedro; Lopes, Susana; Lopes, Joanne; Barroca, Helena; Macedo, Guilherme (Endoscopy International Open, 2021)
Background and study aims The utility of suction during endoscopic ultrasound (EUS) fine-needle biopsy (FNB) using Franseen-tip needle remains unclear and has not been evaluated in randomized trials. We designed a randomized crossover trial to compare the diagnostic yield during EUS-FNB using a 22G Franseen-tip needle, with and without standard suction.Patients and methods Consecutive patients undergoing EUS-guided sampling of solid pancreatic lesions were recruited. A minimum of two passes were performed for each case: one with 20-mL syringe suction (S+) and another without (S–). The order of passes was randomized and the pathologist blinded. The endpoints were the diagnostic yield and the impact of blood contamination in the diagnosis.Results Fifty consecutive patients were enrolled. The overall diagnostic accuracy was 84 %. A diagnosis of malignancy was obtained in 70 samples: 36 in the S+group and 34 in the S–group. A statistically significant difference was seen in the diagnostic accuracy (S+: 78 % vs. S–: 72 %, P < 0.01) and blood contamination (S+: 68 %; S–: 44 %, P < 0.01). The sensitivity, specificity, negative likelihood ratio and positive likelihood ratio for S+vs. S–samples were 76.6 % vs. 73.9 %, 100 % vs. 100 % and 0.23 vs. 0.26, NA vs NA, respectively. A negative impact of blood contamination in the overall diagnostic yield wasn’t seen, even in samples where suction was used (OR 0.36, P = 0.15)Conclusions We found a higher diagnostic yield with the use of suction. It was associated with a higher degree of sample blood contamination that did not affect the diagnostic performance.